The Identification of Three Cancer Stem Cell Subpopulations within Moderately Differentiated Lip Squamous Cell Carcinoma - Ram, Rachna; Brasch, Helen D.; Dunne, Jonathan C.; Davis, Paul F.; Tan, Swee T.; Itinteang, Tinte (Frontiers in Surgery, 2017)
Aim To identify and characterize cancer stem cells (CSCs) in moderately differentiated lip squamous cell carcinoma (MDLSCC). Method MDLSCC samples underwent 3,3-diaminobenzidine (DAB) immunohistochemical (IHC) staining for squamous cell carcinoma marker EMA, CSC marker CD44 and embryonic stem cell markers NANOG, octamer-binding transcription factor 4 (OCT4), spalt-like transcription factor 4 (SALL4), sex-determining region Y-box 2 (SOX2), and phosphorylated signal transducer and activator of transcription 3 (pSTAT3). Immunofluorescent IHC staining was performed on two MDLSCC samples. Western blotting (WB) was used to confirm the expression of the aforementioned proteins and their transcription activation was investigated using NanoString and RT-qPCR. Results IHC staining demonstrated the presence of (1) an EMA+/CD44+/SALL4+/NANOG+/pSTAT3+/SOX2+/OCT4− CSC subpopulation within the tumor nests (TNs); (2) a CD44+/SALL4+/NANOG+/pSTAT3+/SOX2+/OCT4− CSC subpopulation; and (3) a CD44+/SALL4+/NANOG+/pSTAT3+/SOX2+/OCT4+ CSC subpopulation within the stroma, between the TNs. NanoString and RT-qPCR confirmed the presence of mRNA for CD44, SALL4, STAT3, SOX2, and OCT4, and WB confirmed the presence of NANOG, pSTAT3, SOX2, and OCT4. Conclusion This study demonstrates three putative CSC subpopulations within MDLSCC.